Students' Knowledge of Healthy Food and Their Actual Eating Habits: A Case Study on the University of Granada (Spain) - Entrena-Durán, Francisco; Baldan-Lozano, Henar; Valdera-Gil, Juan-Miguel (Frontiers in Sustainable Food Systems, 2021)
This article focuses on an analysis of the discourses produced during 34 semi-structured interviews (17 men and 17 women) conducted at the University of Granada (Spain) with undergraduate, Master, and Ph.D. students. The interviewees were between 20 and 44 years old. It was observed that the fact of having a high educational level did not prevent University students from eating unhealthily. There is a gap between the fact that 97.1% of 34 students interviewed (that is, 33 of them) know what healthy food is and their self-perception about whether or not what they are eating is healthy, since in 41.2% of them said self-perception is negative. This gap narrows as the interviewees' age increases and their socio-economic and vital situation is stabilizing which favors that their eating habits become more regular and healthier. Thus, all the interviewees aged 27 or over self-perceived that they were eating healthily. But the biggest differences are those that have to do with the gender of interviewees. Thus, while 23.5% of women interviewed perceived that they were not eating healthy, 76.5% of them felt that they were eating healthy. However, among the men interviewed, these percentages were somehow reversed, in such a way that 58.8% of them believed that they were not eating healthy, compared to 41.2% of them who indicated that they were eating healthy. Therefore, the investigation revealed that women tend to have the best chances of assuming healthy eating habits. Male students living outside the family home or without female partners exhibited greater feeding problems, while females living under similar conditions tended to display healthier eating habits. This is related to the fact that women have traditionally been in charge of acquiring and preparing food. So, women's food education has not been restricted to the mere transmission to them of knowledge about what healthy food is, but from their childhood they were food trained through their active involvement in practical experiences. Obviously, the solution proposed to this male disadvantage is to not perpetuate macho gender stereotypes that assign women the role of home caregivers, but to seek that both women and men have the opportunity and the duty to experience equally those practical experiences that involve the tasks of the acquisition and preparation of food. Working to achieve a situation like this, not only promotes progress in gender equality, but also helps to overcome the lower training of men to perform the tasks inherent in their diet.